Socio-Cultural Impact and Relevance of Islamic Law in the Matchmaking Tradition in Koto Petai Village, Tanah Cogok Subdistrict, Kerinci Regency - nadia, ghina; Sibawaihi, Muhammad Sibawaihi; Yuliatin, Yuliatin; Mustiah, Mustiah RH; Yogi, Muhammad Yogi Sandra (NALAR FIQH: Jurnal Hukum Islam, 2024)
The tradition of arranged marriage is a social phenomenon that has become part of the culture of many communities, including Koto Petai Village, Tanah Cogok Sub-district, Kerinci Regency, which combines local culture with the principles of Islamic law. In the context of Islamic law, arranged marriages are permissible as long as they fulfill the principle of maslahah and do not violate individual rights, but this practice often conflicts with the freedom to choose a life partner. Previous studies have highlighted the negative impacts of arranged marriage, but few have provided an in-depth analysis of the application of wali mujbir and maqashid al-syariah in the local context. This research uses a qualitative method with a case study approach through in-depth interviews, observation, and analysis of Islamic legal documents. The results showed that arranged marriage can have a positive impact in the form of creating a harmonious family and strengthening relationships between families, but it can also have negative impacts such as psychological pressure, loss of the right to choose a partner, and divorce if done without considering the wishes of the child. This study also found that the principles of maslahah and wali mujbir remain relevant in the practice of matchmaking, but must be implemented with due regard to consent and justice for both parties. The findings provide theoretical contributions in the development of Islamic family law studies as well as practical guidance for managing matchmaking traditions by respecting individual rights, thus creating harmony between traditions and Islamic values.